A novel PSO-CWA algorithm for the estimation of inter-area oscillation parameters - Angrisani, Leopoldo; Bonavolonta, Francesco; Di Noia, Luigi Pio; Lauria, Davide; Liccardo, Annalisa; Tessitore, Salvatore; Ruggiero, Davide (IEEE International Instrumentation and Measurement Technology Conference (Online), 2020)
The paper deals with the analysis of inter-area oscillations, that originates from power transients occurred in high extension grids. The research activity is focused on the implementation of a method capable to provide the manager of the national transmission grid with a tool for real time and accurate monitoring of the power system stability. In particular, the authors present a signal-based algorithm which, starting from the values estimated by the Phasor Measurement Units (PMUs) on the grid, allows the online monitor of the parameters (damping and frequency) characterizing the inter-area oscillations. The proposed algorithm is based on the Particles Swarm Optimization (PSO) method, but the traditional PSO has been enhanced through the use of a Continuous Weighted Average (CWA) which, at each iteration step, filters the PSO outputs assuring the reliability of the estimates.